Improved dynamic power flow model with DFIGs participating in frequency regulation. (24th September 2017) - Li, Shenghu; Zhang, Wei; Wang, Zhengfeng
Summary: The primary frequency regulation of the DFIGs is newly introduced to dynamic power flow to analyze the post‐disturbance power flow and system frequency. Based on the overspeed/pitch angle control, the equivalent inertia of the DFIGs is quantified by their inherent inertia and the adjustable range of the rotor speed, which together with the inertia of the SGs determines the system frequency. With simultaneous solution to the constraints of the DFIGs and power system, the captured power by the wind turbine, the rotor speed, and the slip of the DFIGs are adjusted in dynamic power flow, thus to quantify power loss and active output of the DFIGs, and avoid optimistic judgment to the frequency regulation capability of the DFIGs. With increasing wind power, the wind turbine generators are expected to participate in the frequency regulation to save the burden of synchronous generators (SGs). The primary frequency regulation of doubly fed induction generator (DFIG) using the dynamic power flow is proposed. The equivalent inertia of the DFIG is decided by the inherent inertia and the rotor speed. Its captured power and rotor speed respond to the change of the system frequency. The constraints of the DFIG and power system are solved simultaneously to quantify the active loss of the DFIG. Then, the power flow is solved alternatively with the dynamic equation describing system frequency. The numerical results validate the feasibility of the proposed model and quantify the frequency‐support capability of the DFIG. The proposed model helps to balance the utilization of wind power with the stability of system frequency, while reducing the reserve requirement to the SGs.